Causes of dangerous fungal diseases of potatoes in the western region of Ukraine due to climate change - Andriychuk, T.; Skoreiko, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To determine the species composition of pathogens of potato fungal diseases in the western region of the forest-steppe zone under climatic changes.Methods. Research was conducted during 2021—2022 on the basis of the Ukrainian Plant Quarantine Research Station of the Institute of Plant Protection using laboratory (identification of pathogens) and field (examination of potato plantations and analysis of tuber material) methods.Results. According to the research results, the most common fungal diseases on vegetative plants during the studied period were: anthracnose (Colletotrichum coccodes (Wallr.) S. Hughes), Alternaria solani (Ellis & G. Martin) L.R. Jones & Grout, Alternaria alternata (Fr.) Keissl.), fusarium wilt (Fusarium oxysporum Sсhl.) and late blight (Phytophthora infestans (Mont.) de Bary). As a result of phytopathological analysis of tubers, it was established that the greatest danger during potato storage is caused by pathogens of the genera Fusarium, Phoma, Colletotrichum, Phytophthora, causing fusarium, fomosis, anthracnose, phytophthora and mixed types of rot. the causative agents of fusarium were identified — Fusarium oxysporum Sсhl., F. sambucinum Fuck., F. solani Vart.; phomoza — Rhoma exigua Desm. var. exigua rhizoctonia — Rhizoctonia solani (J. G. Kühn) [teleomorph Thanatephorus cucumeris (A. B. Frank) Donk]; Alternaria solani (Ellis & G. Martin) L.R. Jones & Grout; Alternaria alternata (Fr.) Keissl.; anthracnose — Colletotrichum coccodes (Wallr.) S. Hughes, late blight — Phytophthora infestans (Mont.) de Bary); the share of fusarium was 42.1%, the causative agent of anthracnose — 27.5%.Conclusions. Fungal diseases (anthracnose, fusarium wilt) of potatoes, which at the end of the twentieth century were considered to be of limited distribution, have become widespread, which requires their further study in order to optimize crop protection.